Analisis Pengaruh Corporate Social Responsibility, Intensitas Aset Tetap dan Sales Growth Terhadap Agresivitas Pajak (Studi Empiris Pada Perusahaan Manufaktur Sektor Barang Konsumen Primer (Consumer Non-Cyclicals) Sub-Industri Liquors, Soft Drinks, Dairy Products, Processed Foods yang Terdaftar di BEI Tahun 2017-2021) - Khoirunnasikin Khoirunnasikin; Vivi Iswanti Nursyirwan (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2023)
The purpose of this research is to analyze the effect of corporate social responsibility, fixed asset intensity and sales growth on tax aggressiveness in consumer non-cyclicals sub-industry liquors, soft drinks, dairy products, processed foods manufacturing companies listed on the IDX. This type of research is a quantitative research. This study uses secondary data obtained from the IDX website and the companyâ€™s website. Data collection techniques using literature study and documentation study. The sample of this research is consumer non-cyclicals sub-industry liquors, soft drinks, dairy products, processed foods manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2017-2021. The sample selection used purposive sampling method. The analysis used was panel data regression analysis which was processed using the Eviews application version 9. The results of this research indicate that corporate social responsibility and fixed asset intensity have no effect on tax aggressiveness, sales growth has a negative effect on tax aggressiveness. Corporate social responsibility, fixed asset intensity, and sales growth together (simultaneously) influence tax aggressiveness.Keywords: Corporate Social Responsibility, Fixed Asset Intensity, Sales Growth, Tax AggressivenessÂ